Innate Lymphoid Cells and Natural Killer Cells in Bacterial Infections: Function, Dysregulation, and Therapeutic Targets - Elemam, Noha Mousaad; Ramakrishnan, Rakhee K.; Hundt, Jennifer E.; Halwani, Rabih; Maghazachi, Azzam A.; Hamid, Qutayba (Frontiers in Cellular and Infection Microbiology, 2021)
Infectious diseases represent one of the largest medical challenges worldwide. Bacterial infections, in particular, remain a pertinent health challenge and burden. Moreover, such infections increase over time due to the continuous use of various antibiotics without medical need, thus leading to several side effects and bacterial resistance. Our innate immune system represents our first line of defense against any foreign pathogens. This system comprises the innate lymphoid cells (ILCs), including natural killer (NK) cells that are critical players in establishing homeostasis and immunity against infections. ILCs are a group of functionally heterogenous but potent innate immune effector cells that constitute tissue-resident sentinels against intracellular and extracellular bacterial infections. Being a nascent subset of innate lymphocytes, their role in bacterial infections is not clearly understood. Furthermore, these pathogens have developed methods to evade the host immune system, and hence permit infection spread and tissue damage. In this review, we highlight the role of the different ILC populations in various bacterial infections and the possible ways of immune evasion. Additionally, potential immunotherapies to manipulate ILC responses will be briefly discussed.